SuperSelective primer pairs for sensitive detection of rare somatic mutations - Fred Russell Kramer (Nature Portfolio, 2021)
Abstract SuperSelective primers, by virtue of their unique design, enable the selective exponential amplification of rare DNA fragments containing somatic mutations in the presence of abundant closely related wild-type DNA fragments. However, when a SuperSelective primer is used in conjunction with a conventional reverse primer, linear amplification of the abundant wild-type fragments occurs, and this may lead to a late arising signal that can be confused with the late arising signal from the rare mutant fragments. We have discovered that the use of a pair of SuperSelective primers, one specific for the target mutation in a plus strand, and the other specific for the same mutation in the complementary minus strand, but both possessing 3′-terminal nucleotides that are complementary to the mutation, significantly suppresses the linear amplification of the related wild-type sequence, and prevents the generation of false mutant sequences due to mis-incorporation by the DNA polymerase. As a consequence, the absence of mutant fragments in a sample does not give rise to a false-positive signal, and the presence of mutant fragments in a sample is clearly distinguishable as a true-positive signal. The use of SuperSelective primer pairs should enhance the sensitivity of multiplex PCR assays that identify and quantitate somatic mutations in liquid biopsies obtained from patients with cancer, thereby enabling the choice of a targeted therapy, the determination of its effectiveness over time, and the substitution of a more appropriate therapy as new mutations arise.